Continuous cultivation of Chlorella minutissima 26a in a tube-cylinder internal-loop airlift photobioreactor to support 3G biorefineries. (January 2019) - Tagliaferro, Geronimo Virginio; Izário Filho, Hélcio José; Chandel, Anuj Kumar; da Silva, Silvio Silvério; Silva, Messias Borges; Santos, Júlio César dos
Abstract: Microalgae Chlorella minutissima 26a was cultivated in a tube-cylinder internal-loop airlift photobioreactor under continuous cultivation conditions. The goal was to investigate the influence of different nitrate levels on the growth and composition of microalgae. Three nitrate concentrations (75, 150 and 225 mg L −1 ) were assessed under a fixed flow rate and the outlet flow was analyzed for concentration of biomass, lipid, carbohydrate and protein. Nitrate concentration at higher level (225 mg L −1 ) in the medium promoted biomass growth (188.6 mg L −1  d −1 ) and lipid production (92.8 mg L −1  d −1 ), and decreased carbohydrate amount (29.1 mg L −1  d −1 ) without any change in protein content (37.7 mg L −1  d −1 ). Use of tube-cylinder internal-loop airlift photobioreactor in continuous mode could be a promising approach in algal biorefineries so called 3G biorefineries, resulting in high biomass productivity in a simple cultivation system. Highlights: Continuous cultivation in tube-cylinder internal-loop airlift photobioreactor. Effect of nitrate concentration in biomass composition of C. minutissima . Increased nitrate concentration resulting in higher lipid content. Nitrate repletion resulted in higher biomass and lipid productivity. Evaluation of a promising system for microalgae biorefineries.